Effect of Absorption Layer on Interior Sound Field of Sonar Dome - 程钊 陶猛 范军 (Shanghai jiao tong da xue xue bao, 2010)
Using the finite element method （FEM） and boundary element method （BEM） and considering the sound absorption layer which is covered on the backing of the sonar dome, the interior field in the dome which is excited by the incident plane wave has been studied. This method is validated by comparing numerical results with that of classic elastic theory. Then the effect of parameters of the sound absorption layer on interior sound field has been analyzed. The numerical calculation results show that uniformity of interior sound pressure is improved when the backing is covered with a sound absorption layer. The thicker the layer is, or the higher the loss factor of layer is, the more uniform the sound field is.